Gender diversity on corporate boards and earnings management: Evidence for European Union listed firms - Sandra Alves (Cogent Business & Management, 2023)
Using a sample of 3.808 non-financial European Union listed companies from 2011 to 2020, this study extends previous research by empirically examining how board gender diversity affects the magnitude of earnings management. The results support the predicted (negative) relationship between female directors and earnings management. We also find that when a critical mass of three or more female directors is reached, they can have a voice, which can have a positive impact on earnings quality (less earnings management). The results based on this study offer useful information for regulators in European Union countries. The results also provide useful information to investors in evaluating the impact of board gender diversity on earnings quality. The major contribution of the current study is that in contrast to similar studies, we also present our evidence by country. In addition, we test the critical mass hypothesis to evaluate the ability of female directors to impact earnings management based on their numerical representation on the board of directors, an issue that has drawn reduced attention from empirical studies.
Keywords: 650; Female directors; critical mass theory; earnings management; discretionary accruals